PENGAWASAN PEMERINTAH DAN MASYARAKAT DALAM KETERSEDIAAN PRASARANA, SARANA, DAN UTILITAS UMUM PERUMAHAN KOTA KUDUS (STUDI KASUS PERUMAHAN BUMI RENDENG BARU) - Muchamad Syaifudin .; Purwoko . .; Lusia Astrika . (Journal of Politic and Government Studies, 2017)
“Government and Community Supervision In Availability Infrastructure, Infrastructure and Public Utilities in the Holy City Housing (housing case studies Rendeng New Earth)"Act No. 1 of 2011 on Housing and Settlement Region. The settlements were comfortable and attractive place to live can be created through the provision of social facilities (fasos) and public (and public) is complete and sufficient. The provision of such facilities is absolutely necessary as a means of social interaction to create a comfortable and attractive city. Fasos and fasum is a facility that is needed by society in a residential area. The facility can be educational, health, shopping, worship, recreation and culture, sports, and other undertaken by the government and the people holy to the housing district BRB is a form of preventive measure to reduce fraud by owners of housing. Where supervision is done by the BPN, the Office of the Holy Ciptakaru and the public to minimize it so that the owner does not abide by the rules and do whatever they like uu No. 1 of 2011 on housing where good housing facilities must meet social and public facilities.This study uses a qualitative approach. The results showed Monitoring carried out by the government is not balanced. Where supervision is more emphasis on preventive supervision that is only on the mechanism of licensing. While on supervision repressive enough in enforcing the rules or policies. On the preventive supervision is mostly done through the granting of licenses. While from the public on preventive supervision, community coordinated by way of the Council at the meeting each month in an event gathering BRB housing residents. In a repressive surveillance society asks a lot of its aspirations to residential owners and do not forget to relevant agencies regarding Fasum housing and social facilitiesResearchers are aware of this research is far from perfection, the researchers then expected to develop this research with triangulation method so that the research results more accurate. Keywords: BRB Housing, Infrastructure Facilities and Utilities